Mainstreaming Shari'ah solutions for peace and justice: Al-Mizan as the foundation of the legal system - Abdul Ghani Azmi, Ida Madieha (2021)
The Islamic Legal System cluster (ILSC) envisions a transition from a dual legal system to a seamless non-hierarchical legal system where the Shari’ah legal system is at par with the civil system and opened to all Malaysians as the preferred choice for settling legal disputes. This would enable Malaysians to choose where to bring their disputes and ideally, the Shari’ah legal system will be the preferred choice as it embodies a complete system that ensures justice and fairness for all. This reflects the spirit of the Shari’ah as Rahmatan lil alamin.